Frequency domain model of an electric vehicle charger for fast simulation - Gheorghe Alexandru Gabriel; Maricaru Mihai; Neacșu Mihăiță Gabriel (E3S Web of Conferences)
Electric vehicles (EVs) are becoming more and more common in many countries. They use rectifiers based on power electronics to charge their batteries, which are a source of current harmonics that can significantly affect the power quality of low-voltage (LV) and medium-voltage (MV) grids. Harmonic emissions from EV charging stations, which are strongly affected by and also affect the distortion of the supply voltage, are of particular concern. Several EV charger models are in the literature, but they consist of complex circuits and are very time-consuming to simulate. A simplified, accurate, easy-to-build, and fast-to-analyze model would help assess the harmonic pollution of the grid. This paper proposes a frequency domain (FD) model based on the measured RMS and phase of a specific number of current harmonic components. It consists of four sets of polynomials that relate the output direct current (DC) to the three-phase input voltage components. Three sets of polynomials represent the three- phase input phases, while one set represents the output port of the EV charger. The model is implemented in software operating in the frequency domain and is validated by comparing the resulting current waveforms with the measured waveforms that were used to develop the model.